Reading for Education: The Role of Libraries - Dadzie, P.S. (Ghana Library Journal, 2008)
This paper examines the role reading plays in creating independent learners, reducing illiteracy in society and helping people understand themselves and others better. It highlights the relationship between reading and education and stresses the role that libraries play as one of the key stakeholders in promoting the culture of reading. The paper also presents experiences of reader developments and reading promotions from libraries of developed and developing countries. Some challenges in inculcating the culture of reading in libraries of developing countries are also highlighted. Recommendations are made for sustaining the culture of reading in developing countries.